2017
DOI: 10.1002/ajh.24593
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic issues in transgender medicine: A review

Abstract: Clinicians, including hematologists, are more frequently encountering transgender individuals in practice; however, most lack training on the management and complications of transgender medicine. Hormonal therapy forms the backbone of medical interventions for patients undergoing gender transition. While supplementing an individual's intrinsic sex hormone is associated with a variety of hematologic complications including increased rates of venous thrombosis, cardiovascular events, erthyrocytosis, and malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 54 publications
0
74
0
4
Order By: Relevance
“…However, there have been no prospective, randomised controlled trials evaluating oral versus transdermal estradiol in any population (transgender or postmenopausal women), and any observational case–control studies have been conducted on relatively high‐risk populations in postmenopausal women . One large population‐based study of postmenopausal women has shown a similar increased risk of stroke when comparing oral estradiol and high‐dose (>50 mcg/day) transdermal estradiol – those typically used in trans females; however, in contrast, meta‐analyses suggest that transdermal oestrogens carry minimal or no thrombotic risk, with minimal effects on haemostatic variables . Without data for the transgender population specifically, we must extrapolate based on studies of postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been no prospective, randomised controlled trials evaluating oral versus transdermal estradiol in any population (transgender or postmenopausal women), and any observational case–control studies have been conducted on relatively high‐risk populations in postmenopausal women . One large population‐based study of postmenopausal women has shown a similar increased risk of stroke when comparing oral estradiol and high‐dose (>50 mcg/day) transdermal estradiol – those typically used in trans females; however, in contrast, meta‐analyses suggest that transdermal oestrogens carry minimal or no thrombotic risk, with minimal effects on haemostatic variables . Without data for the transgender population specifically, we must extrapolate based on studies of postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…For this diver, a priori, there was therefore no medical contraindication against diving. It should be borne in mind, however, that the embolic risk is increased among transgender people [20]. The physician should be vigilant and stay informed of scientific advances in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the studies were small and very short in follow-up time. 47 Furthermore, many venous thrombotic events are likely to be under-reported. Data from early studies in transgender women in the Netherlands suggested a high lifetime prevalence (about 5% over a mean of 10 years of follow-up) of thromboembolic disease.…”
Section: Comorbidities and Pitfallsmentioning
confidence: 99%